(NmETODIKA OBU^ENIQ SOLXNOMU PENI@(B.s (Nu^EBNOE POSOBIE(B.s - (Na(B.(Ng(B.(NmENABINIs ((NmOSKWAs (NpROSWE]ENIE(B.s, 1987)
(Nw POSOBIE RASSMATIWA@TSQ PRINCIPY I METODY WOKALXNOGO OBU^ENIQ RAZWITIQ WOKALXNOGO PEW^ESKOGO O SPOSOBAH OWLADENIQ TEHNI^ESKIMI NAWYKAMI PENIQ(B.s
Keywords: (NmETODIKAs